2022
DOI: 10.1016/j.jshs.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in outdoor physical activity under ambient fine particulate matter pollution: A risk-benefit analysis

Abstract: Highlights A risk-benefit analysis was performed to estimate the optimal outdoor moderate physical activity (MPA) duration under varying particulate matter (PM 2.5 ) concentrations. An inverse nonlinear relationship was identified between optimal MPA duration and background PM 2.5 concentration levels. The relationship between optimal MPA duration and background PM 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…The evidence that the impacts of climate change have dramatic consequences for human physical activity behaviors has been supported in previous studies [37]. Ambient air pollution was associated with a decline in PA in this study, which is in agreement with prior research conducted in China and in locations outside of China [23,32,38]. An et al showed that higher ambient PM 2.5 air pollution discourages PA among US older adults [38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The evidence that the impacts of climate change have dramatic consequences for human physical activity behaviors has been supported in previous studies [37]. Ambient air pollution was associated with a decline in PA in this study, which is in agreement with prior research conducted in China and in locations outside of China [23,32,38]. An et al showed that higher ambient PM 2.5 air pollution discourages PA among US older adults [38].…”
Section: Discussionsupporting
confidence: 92%
“…Ambient air pollution was associated with a decline in PA in this study, which is in agreement with prior research conducted in China and in locations outside of China [23,32,38]. An et al showed that higher ambient PM 2.5 air pollution discourages PA among US older adults [38]. In China, Tainio et al showed that the pooled effects of high air pollution reduced PA in children and adults [30].…”
Section: Discussionsupporting
confidence: 92%
“…Air pollution levels observed in some agglomerations, revealing parameters similar to smog conditions, seem to prevail in terms of health impacts over problems caused by food or water pollution. So far, a lot of emphasis has been placed on these issues in the scientific literature [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%